2023
DOI: 10.2147/jir.s406907
|View full text |Cite
|
Sign up to set email alerts
|

Sparcl1 and Atherosclerosis

Abstract: Atherosclerosis and its complications constitute some of the major diseases affecting humans worldwide. A core component of atherogenesis is endothelial cell damage and dysfunction, which also includes factors such as adhesion and proliferation of various cells. Multiple studies have shown that atherosclerosis and cancer share a common pathophysiological process and exhibit a degree of similarity. Sparcl-1 is a cysteine-rich secretory stromal cell protein present in the extracellular matrix and belongs to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…As a result, a total of 955 DEGs were identified. [99], AZGP1 [100], CYP1B1 [101], PRRX1 [102], CD34 [103], A2M [104], CDKN2A [105], SERPINE1 [106], CD44 [107], FABP4 [108], ITGB3 [109], ALOX5AP [110], DAND5 [111], SFRP4 [112], RUNX2 [113], TACR3 [114], MYD88 [115], CYBA (cytochrome b-245 alpha chain) [116], STAT6 [117], FOXC1 [118], FN1 [119], TLR6 [120], CAV1 [121], RGS4 [122], TPM2 [123], TNFSF4 [124], LOX (lysyl oxidase) [125], SMOC2 [126], SPHK1 [127], FOLH1 [128], CYP2C8 [129], CD163 [130], DIRAS3 [131], OSMR (oncostatin M receptor) [132], POSTN (periostin) [133], SELL (selectin L) [134], TMPRSS2 [135], FLNC (filamin C) [136], CXCL16 [137], APOBR (apolipoprotein B receptor) [138], COL6A2 [139], LTBP2 [140], SPARCL1 [141], FOSL2 [142], ISL1 [143], HTR2C [144], TNNT2 [145], HGF (hepatocyte growth factor) [146], IL33 [147], SYK (spleen associated tyrosine kinase) [148], ADRB1 [149], CMKLR1 [150], SHOX2 [151], MEG3 [152], SCUBE1 [153...…”
Section: Discussionmentioning
confidence: 99%
“…As a result, a total of 955 DEGs were identified. [99], AZGP1 [100], CYP1B1 [101], PRRX1 [102], CD34 [103], A2M [104], CDKN2A [105], SERPINE1 [106], CD44 [107], FABP4 [108], ITGB3 [109], ALOX5AP [110], DAND5 [111], SFRP4 [112], RUNX2 [113], TACR3 [114], MYD88 [115], CYBA (cytochrome b-245 alpha chain) [116], STAT6 [117], FOXC1 [118], FN1 [119], TLR6 [120], CAV1 [121], RGS4 [122], TPM2 [123], TNFSF4 [124], LOX (lysyl oxidase) [125], SMOC2 [126], SPHK1 [127], FOLH1 [128], CYP2C8 [129], CD163 [130], DIRAS3 [131], OSMR (oncostatin M receptor) [132], POSTN (periostin) [133], SELL (selectin L) [134], TMPRSS2 [135], FLNC (filamin C) [136], CXCL16 [137], APOBR (apolipoprotein B receptor) [138], COL6A2 [139], LTBP2 [140], SPARCL1 [141], FOSL2 [142], ISL1 [143], HTR2C [144], TNNT2 [145], HGF (hepatocyte growth factor) [146], IL33 [147], SYK (spleen associated tyrosine kinase) [148], ADRB1 [149], CMKLR1 [150], SHOX2 [151], MEG3 [152], SCUBE1 [153...…”
Section: Discussionmentioning
confidence: 99%
“…The secreted protein acidic rich in cysteine-like 1 (SPARCL1), also known as Hevin, MAST9, SC1 and ECM2, is a matricellular protein which is a member of SPARC-related protein family [ 8 ]. SPARC family members could be secreted into the ECM and play different roles in regulating cell adhesion, proliferation, metastasis, and growth factor signaling to affect the extracellular matrix (ECM) and interactions between cells [ 9 ]. Studies have revealed that SPARCL1 is an adhesion molecule mediating the cell–matrix interactions and participates in physiological processes such as cell adhesion, differentiation and proliferation [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] It can regulate cell-matrix interactions and participates in tissue remodeling. [25][26][27] Compelling evidence has confirmed that matricellular proteins are the important regulators of neuronal integrity. [28][29][30] As such, SPARCL1 could impact synaptic stability and may play a pivotal effect in axonal regeneration after acute brain injury.…”
mentioning
confidence: 99%